1995
DOI: 10.1159/000188592
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ketanserine in Cyclosporine-lnduced Renal Dysfunction in Rats

Abstract: Cyclosporine (CsA)-treated female Wistar rats, in dose of 37.5 μM (45 mg)/ kg/day for 7 days, exhibited significantly decreased creatinine clearance (Ccr), and provoked body weight loss (BWL), which is consistent with the development of nephrotoxicity (NT). Urine volume (V) did not change and proteinuria (PU) was not provoked. These changes were associated with significantly diminished ratios of urinary PGE2/TXB2 and 6kPGF/TXB2 excretions. Light-microscopic (LM) se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…In this model we investigated a potential protection by levemopamil (L), a calcium channel blocker with 5-HT (5-HT2) receptor antagonist activity (Hofmann et al, 1989). This drug has been shown previously in rats to preserve the function of the transplanted kidney following warm and cold ischaemia (Mills et al, 1987) or to protect the kidney from cyclosporine-induced damage (Darlametsos et al, 1995). It also reduced infarct size following cerebral artery occlusion (Nakayama et al, 1988).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In this model we investigated a potential protection by levemopamil (L), a calcium channel blocker with 5-HT (5-HT2) receptor antagonist activity (Hofmann et al, 1989). This drug has been shown previously in rats to preserve the function of the transplanted kidney following warm and cold ischaemia (Mills et al, 1987) or to protect the kidney from cyclosporine-induced damage (Darlametsos et al, 1995). It also reduced infarct size following cerebral artery occlusion (Nakayama et al, 1988).…”
Section: Discussionmentioning
confidence: 90%
“…More recently, 5-HT was demonstrated to be a potent vasoconstrictor in the kidney (Endlich et al, 1993) and also to play a pathogenetic role in acute clinical (Sidel'nikov & Sivoraksha, 1990) and experimental renal damage (Darlametsos et al, 1995). 5-HT is released from enterochromaffin cells and, more importantly, from platelets, but may also be produced in proximal tubule cells (Sole et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data clearly indicated that urinary TxB 2 was lower in both the normal and postischaemic kidney of WF rats, whereas excretion of the vasodilator PGE 2 , the main prostanoid in the kidney, was similarly increased in both WH and WF rats. The ratio between vasodilator (PGE 2 ) and vasoconstrictor (TxA 2 ) autacoids, which is routinely used as an indicator of the direct role of vasoconstrictor factors in the development of renal failure, [52][53][54] appeared to be higher in WF than WH rats after I/R. Interestingly, COX-2 activity has been reported to depend on nNOS activity.…”
Section: Discussionmentioning
confidence: 99%
“…[1,2] CsA nephrotoxicity is characterized by intense renal vasoconstriction that induces a fall in renal blood flow and in the glomerular filtration rate. Morphological changes to the kidney, consisting of tubular diffusion vacuolization, single-cell necrosis, [9] and microcalcification are fully reversible. However, even with normal blood levels or during long-term dosage, CsA can produce chronic hypertension and can be the cause of irreversible impairment of renal function.…”
Section: Introductionmentioning
confidence: 99%